Utilizing prospective sequence analysis of SHH, ZIC2, SIX3 and TGIF in holoprosencephaly probands to describe the parameters limiting the observed frequency of mutant gene x gene interactions - Roessler, Erich; Vélez, Jorge I.; Zhou, Nan; Muenke, Maximilian (Molecular genetics and metabolism, 2012)
Clinical molecular diagnostic centers routinely screen SHH, ZIC2, SIX3 and TGIF for mutations that can help to explain holoprosencephaly and related brain malformations. Here we report a prospective Sanger sequence analysis of 189 unrelated probands referred to our diagnostic lab for genetic testing. We identified 28 novel unique mutations in this group (15%) and no instances of deleterious mutations in two genes in the same subject. Our result extends that of other diagnostic centers and suggests that among the aggregate 475 prospectively sequenced holoprosencephaly probands there is negligible evidence for direct gene-gene interactions among these tested genes. We model the predictions of the observed mutation frequency in the context of the hypothesis that gene x gene interactions are a prerequisite for forebrain malformations, i.e. the “multiple-hit” hypothesis. We conclude that such a direct interaction would be expected to be rare and that more subtle genetic and environmental interactions are a better explanation for the clinically observed inter- and intra-familial variability.